A bacterial consortium isolated from an Icelandic fumarole displays exceptionally high levels of sulfate reduction and metals resistance - Alexandrino, Maria (2018)
The soils of three fumaroles and one mining site, all with high metal content, were surveyed for the presence of metal-resistant sulfate-reducing bacteria and their potential application in the bioremediation of acid mine drainages. By means of selective soil enrichments a bacterial consortium was isolated from an Icelandic fumarole that displayed very high sulfate reduction in the presence of a mixture of 0.75 g/L of Fe, 0.20 g/L of Zn and 0.080 g/L of Cu. Under these conditions the bacterial consortium reduced 91% of the added 3.9 g/L of sulfate after 28 days, precipitating 100% of the Fe, 96% of the Zn and 97% of the Cu during the same time. Both total bacterial numbers and numbers of culturable sulfate-reducing bacteria remained unchanged when grown in media containing metals, suggesting low or absent inhibitory effects of the metals on the bacterial consortium. PCR-DGGE profiles of the sulfate reducing bacterial communities obtained from the Icelandic fumarole sample showed that bacterial diversity decreased significantly after metal addition: from the original 12 ribotypes only two were detected in the metal-tolerant culture. Phylogenetic analysis of 16S ribosomal RNA gene sequences revealed that these two ribotypes were affiliated with the genera Clostridium and Desulfovibrio, with C. subterminale, C. pascui, C. mesophilum and C. peptidovorans and D. desulfuricans identified as their closest relatives.